Information content and informativeness of the analyst report in Malaysia - Mohd Thas Thaker, Hassanudin *; Mohamad, A.; Mustaffa Kamil, N. K.; Duasa, J. (Emerald, 2020)
Purpose: This paper aims to investigate the value of information content and informativeness of the analyst report for Sharīʿah-compliant shares in Malaysia. Design/methodology/approach: The authors use a sample of 657 daily published analyst reports on Sharīʿah-compliant shares from 2010 to 2015, which were downloaded from Bursa Malaysia’s repository system. The method was quantitative in nature and panel regression analysis was used. Diagnostics tests including the variance inflation factor, correlation analysis, heteroskedasticity test, serial auto-correlation and the Hausman test were performed to ensure validity and reliability of data. The significance of the variables indicated whether the analyst reports contained valuable information on Shariah compliancy. Findings:Results obtained from the FEM-Robust model revealed that the R2 value was equivalent to 0.79 per cent, suggesting that the power of return explained by the information content and informativeness was less for Sharīʿah-compliant shares. The F-statistics were statistically significant for all models, postulating that the data used were reliable and fit for the purpose of analysis. The findings showed that the information content of target price and earnings forecasts significantly influenced the returns of Sharīʿah-compliant shares. In terms of informativeness, return on equity, sales to price ratio and cash flow to price were associated with the returns of the shares. Practical implications: The outcome from this finding confirmed that the analyst report retained its position as a good source of reference when making investment decisions. However, the disclosure of information in the form of qualitative information together with fundamental information should be enhanced for Sharīʿah-compliant share so that investors would have adequate information when making an investment decision. Originality/value: This study will supply more insights into the matter of information content and informativeness of the analyst report in Malaysia by focussing on Sharīʿah-compliant shares, which is practically an underexplored research area in Malaysia.